Olfactory dysfunction in COVID-19; Self-report or Olfactory Dysfunction Test? - Elham Sahebalzamani; Shayan alijanpour; Payam Saadat (Babol University of Medical Sciences, 2025)
Background: COVID-19 developed a sudden onset of smelling disorders. Researchers used self-reported or special tests to study this issue. We aimed to investigate whether quantitative-test smell disorders have a considerable difference from self-reported or not. Methods: We searched 554 studies published between December 2019 to September 2020 by the PICO model. Our search strategies were based on MeSH terms in the electronic databases Web of Science (136 articles), Scopus (84 articles), and PubMed (334 articles). The duplicated articles were excluded, then the preferred reporting items for systematic reviews and meta-analysis guidance were utilized. Finally, we divided the studies into two (self-report (33 articles) and specific-test (9 articles)) groups. Results: 33 (80%) articles expressed olfactory dysfunction by self-report of patients and 9(20%) studies were conducted by a specific test. Only three studies, one in self-report; ((internal reliability, Cronbach α = 0.84) and validity (r = -0.60, p < 0.001)) and two in specific-test groups; ((test-retest r=0.94) and another study (test-retest r >0.7)) conducted validity and reliability. Self-reported studies published a various range of prevalence (20% _97%) in patients with COVID-19. COVID-19 patients with a specific-test group were found to have a primary incidence of anosmia of over 65%, even reaching 98% depending on the types of tests. Conclusion: Self-reporting of COVID-19 detection can be affected by sociodemographic factors. Although self-reported questionnaires are economical and easy to use, standardized tests provide more reliable comparisons and professional assessments. Therefore, standardized tests are recommended for more accurate screening over self-reporting.